2003
DOI: 10.1081/jdi-120024299
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability, Left Ventricular Functions, and Cardiac Autonomic Neuropathy in Patients Undergoing Chronic Hemodialysis

Abstract: As a result, the dependence of cardiac autonomic neuropathy on the disease duration and degree of left ventricular function impairment was shown in the patients undergoing chronic hemodialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…This suggested that slight increases in the WHR in obese individuals could increase their risk of cardiovascular morbidity and mortality through CAN [18]. Obesity causes a reduction HRV indices consistent with a reduction in PNS activity that disrupts the normal maturation of cardiac autonomic control in healthy obese children [20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…This suggested that slight increases in the WHR in obese individuals could increase their risk of cardiovascular morbidity and mortality through CAN [18]. Obesity causes a reduction HRV indices consistent with a reduction in PNS activity that disrupts the normal maturation of cardiac autonomic control in healthy obese children [20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…Besides left ventricular hypertrophy, systolic and diastolic dysfunction, interstitial fibrosis, and autonomic neuropathy were found among patients with end stage renal disease [36, 37]. …”
Section: Renal Diseasementioning
confidence: 99%
“…Patients with ESRD undergoing chronic hemodialysis is usually present a dysfunction of the ANS, exhibited as low parasympathetic/vagal modulation associated with high sympathetic modulation of the heart rate assessed by heart rate variability (HRV) analysis [6][7][8] . Several previous studies have used HRV parameters based on traditional linear HRV analysis to predict patient outcomes and found that lower HRV is related to an increased risk of cardiovascular and all-cause mortality in patients with ESRD receiving chronic hemodialysis [9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%